Responding to Digital Transformation by External Corporate Venturing: An Enterprising Family Identity and Communication Patterns Perspective - Reinhard Prügl; Dinah Isabel Spitzley (Journal of Management Studies, 2021)
Digital transformation increasingly requires activities located outside firm boundaries, for example via alliances with start-up companies. Despite this, German Mittelstand firms, primarily owned and managed by enterprising families and seen as role models of innovation, appear reluctant to place strategic emphasis on venturing outside the firm's boundaries when it comes to digital transformation. Drawing on the concepts of identity and communication patterns, we theorize on the mechanisms behind this behaviour. Applying structural equation modelling to a sample of 254 members of the next generation in enterprising families from Germany, we find that family communication patterns impact the strategic priority for or against external corporate venturing via identity-related considerations.
Keywords: 650; digital transformation; enterprising families; external corporate venturing; identity; family communication patterns